234k views
1 vote
What does x equal in the equation 4x + (−3) = 5x + 3?

2 Answers

2 votes

Answer:

x = -6

Explanation:

4x + (−3) = 5x + 3

+3 +3

4x = 5x + 6

-5x -5x

-x = 6

÷(-1) ÷(-1)

x = - 6

User Pratibha Sarode
by
5.1k points
4 votes

Answer:

x = -6

Explanation:

First write the equation.

4x + -3 = 5x + 3

The isolate x in the equation. Add -4x to both sides.

4x + -3 + -4x = 5x + 3 + -4x

-3 = x + 3

Then add -3 to both sides.

-3 + -3 = x + 3 + -3

-6 = x

Now you have the value of x = -6.

Cheers.

User Derrrick
by
4.0k points